Ultrastructural study of osteodentin formation induced by irradiation - Itoiz, María Elina; Lanfranchi, Héctor E.; Cabrini, Rómulo Luis (1983)
Fil: Itoiz, María Elina Comisión Nacional de Energía Atómica; Argentina